Design of parabolic solar dish tracking system using arduino - Rahimoon, Asif Ahmed; Abdullah, Mohd Noor; Soomro, Dur Muhammad; Nassar, Murad Yahya; A. Memon, Z.; Shaikh, P.H. (Institute of Advanced Engineering and Science (IAES), 2020)
This paper demonstrates the designing parameters of a solar parabolic dish prototype for rustic areas with great solar irradiance rate availability, where have no access of electricity services or low-income people survives to buy a stove (electric or gas). The solar parabolic dish prototype intends a solution against these types of remedies and pursues solar light to work. The parabolic dish has a polished surface, where the solar radiations fall and collected at a single concentrated focal point. At this point the collected form of energy is used to derive different thermal applications like as; cooking & heating with single and dual axis schemes. This paper discusses the important stages of dual axis prototype; implementation, solar location strategy, the analysis in terms of theory, structural design & material. The dual axis prototype is implemented through the help of Arduino chipboard that is easily in maintenance, along with that this prototype is configured with anti-lock H-bridge (L298) module to overcome the control circuit complexity and AVR modules. Two rotational motors of 12V are installed on 4*4ft designed aluminum frame with a dual-axis tracking system. The jerks among trackers are also reduced with this prototype which maintains the experimental declination angle about 22.47°.To finish, this paper results that parabolic solar dish tracker obtains 3.43% improved power efficiency in comparison of photovoltaic panel tracker.